SELF-PERCEIVED COMPETENCE OF NEW DENTAL GRADUATES IN PAKISTAN – A MULTIINSTITUTION STUDY: Competence of new dental graduates - Qazi, Haroon Shahid; Ali, Kamran; Cockerill, Josephine; Zahra, Daniel; Raja, Ulfat Bashir; Ataullah, Khurram (Pakistan Armed Forces Medical Journal, 2021)
Objective: To investigate the self-perceived competence of house-officers from three dental institutions in Pakistan. Study Design: Cross-sectional study. Place and Duration of Study: Islamabad Dental Hospital, Fatima Memorial Dental Hospital and Islamic International Dental Hospital, from Jan to Dec 2018. Methodology: House-officers from three dental institutions were invited to participate in a cross-sectional study. A previously validated preparedness assessment scale was used to gauge the perceptions and experiences of the participants on a range of clinical, cognitive and affective skills. The results were compared to data from Dental Foundation Trainees in the UK. Results: In total 128 house-officers responded to the online questionnaire (18 participants were excluded due to missing data). All but four participants were in the 20-25 years age group (96.4%). The mean overall score of participants was 70/100 (SD ± 11.71). Self-perceived competence was reported to be low for clinical skills in radiography, crowns, cast-partial dentures and endodontics on multi-rooted teeth. Conclusions: This study investigated self-perceived competence amongst new graduates and provides information for comparison with data from Foundation Dentists in the UK. Pakistani House-Officers felt less prepared than Dental Foundation Trainees in 49/50 attributes. Several areas were identified where graduates from both countries may benefit from further education, training and consolidation. The findings may be of interest to dental educators and other stakeholders. Keywords: , , ,